PEMANFAATAN LOKASI TAMBAK KAWASAN ALUE NAGA ACEH BESAR UNTUK PENGEMBANGAN BUDIDAYA RUMPUT LAUT JENIS GLACILARIA MENGGUNAKAN FLOATING HOUSE METHOD DALAM MENDUKUNG KETAHANAN PANGAN - Ichsan Setiawan; Sarwo Edhy Sofyan; Akram Tamlicha (Universitas Teuku Umar, 2020)
Aceh Province is an area surrounded by coasts which has great potential to develop marine product cultivation, one of which is seaweed. In line with the goal of the central government in 2018 stating its support for increaseing seaweed cultivation in Aceh Province. Meanwhile, the Ministry of Maritime Affairs and Fisheries' Directorate General of Cultivation stated that so far the seaweed industry and cultivation are still constrained by transportation problems for marketing. Based on the results of research in a number of regions in Indonesia, it is explained that the coastal area of Aceh is an area that has very good potential for the seaweed cultivation. This study focuses on the Glacilaria sp seaweed cultivation due to its easiness to grow in community ponds. The drawback of this pond cultication method is the existence of predators that eat seaweed and the pond bottom mud that pollutes the seaweed. The application of floating house technology for glacilaria seaweed culture is seen as a solution for aforemention problems. This technology protects the seaweed from predators and the contamination of the seawee from mud pond. The proposed sea seaweed cultivation method is anticipated to offer better income and improve the quality of life of the community, especially in the the targeted area, Alue Naga. Regarding the current situation, Farmer in Alue Naga still practice the conventional method for cultivating the seaweed in the land pond. This regular method has the shortcoming in protecting the seeweed from the predators. In addition, due to the seaweed attached to the bottom of the pond, it causes the slow growth of seaweed. These circumstances cause the crops have lower quality, result in a hardly marketable product either for national or international markets. To cope with such conditions, an easy to use, reliable and safety floating house was proposed and built for the use of glacilaria seaweed culture. The community is also engaged in the workshop and construction of floating house for the glacilaria seaweed culture taught by staff of Cot Irieh Fiberlass workshop. This engagement aims to increase the insight and skill of the community regarding construction and maintenance of the glacilaria seaweed culture floating house. This study is fully supported by Syiah Kuala University Research and Community Service Institute through fostering the Alue Naga fishing community through direct application of technology.